Pengembangan Bakat dan Minat - Khothibul Iman (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract This study show that in the development of the talent of a child, to note a few things, among them: (1) caution; (2) motivation; (3) support; (4) knowledge; (5) exercise; (6) award; facility; (8) environment; (9) cooperation; and (10) good examples. The interests of a child include feelings of pleasure or interst in the objects that make someone pay attention to favored objects well as their knowledge about an object. To recognize student who are gifted and have interest, the subject's teacher or class teacher is the most reliable, because every time they intercommunicate with students. There are several kinds of talent development program and interests of students that can be applied in school. First, the enrichment. Providing opportunities and facilities that are deeping the additional learning to gifted students after completing the regular task. Second, accelaration. Students are allowed to jumping class, or complete the regular program within a shorter time. Third, a special grouping, wich gives children the opportunity spesifically to gain learning experiences that match their interest and potential. Fourth, review of research institutions and development or the provision of assistance gifted students. Keywords talent, enthusiasm, talent development program, gifted students